1992
DOI: 10.1002/jez.1402630108
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of high stocking density and triiodothyronine‐administration on aspects of the in vivo intermediary metabolism and in vitro hepatic response to catecholamine and pancreatic hormone stimulation in brook charr, Salvelinus fontinalis

Abstract: Brook charr (Salvelinus fontinalis) were maintained at one of two stocking densities (SD) (30 or 120 kg/m3) and fed either a control or a T3-supplemented (20 mg/kg) diet for 30 days in order to investigate possible interactive effects of SD and T3-administration on growth, feeding rate, food conversion efficiency, and hepatic and dark muscle enzyme activity. In addition, liver slices were incubated in vitro for 6 h with epinephrine, norepinephrine, isoproterenol, propranolol, insulin, glucagon, or somatostatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Several studies have found the densityrelated alterations in pituitary-thyroid axis when investigating the influences of stocking density on fish behavior, development, and growth (Leatherland and Cho 1985;Schreck and Patino 1985;Vijayan and Leatherland 1988;Scott-Thomas et al 1992). At high stocking density, decreases in both growth rate and plasma T 4 level were observed both in rainbow trout (Oncorhynchus mykiss) (Leatherland and Cho 1985) and in brook charr (Vijayan and Leatherland 1988).…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have found the densityrelated alterations in pituitary-thyroid axis when investigating the influences of stocking density on fish behavior, development, and growth (Leatherland and Cho 1985;Schreck and Patino 1985;Vijayan and Leatherland 1988;Scott-Thomas et al 1992). At high stocking density, decreases in both growth rate and plasma T 4 level were observed both in rainbow trout (Oncorhynchus mykiss) (Leatherland and Cho 1985) and in brook charr (Vijayan and Leatherland 1988).…”
Section: Discussionmentioning
confidence: 95%
“…Stocking density did increase plasma cortisol levels and this coincided, indeed, with hyperglycaemia and decreased liver glycogen content in the wedge sole. Cortisol‐induced changes in hepatic glycogenolitic potential, gluconeogenic capacity and glucose export capacity may be the basis of this observation (Vijayan, Ballantyne & Leatherland 1990; Scott‐Thomas, Ballantyne & Leatherland 1992; Vijayan, Pereira, Grau & Iwama 1997; Laiz‐Carrión, Sangiao‐Alvarellos, Guzmán, Martín del Rio, Míguez, Soengas & Mancera 2002; Trenzado, Carrick & Pottinger 2003; Laiz‐Carrión, Guzmán‐Jiménez, Martín del Río & Mancera 2005; Sangiao‐Alvarellos, Guzmán, Laíz‐Carrión, Míguez, Martín del Río, Mancera & Soengas 2005). However, plasma glucose values did not increase in fish kept at the highest density.…”
Section: Discussionmentioning
confidence: 98%
“…Plasma T 4 and T 3 concentrations were measured using the Amerlex solid phase radioimmunoassay kits (Johnson & Johnson Clinical Diagnostics, Markham, ON, USA) previously described and validated for use with various salmonid species, including brook charr, Salvelinus fontinalis (Linnaeus) (Scott‐Thomas, Ballantyne & Leatherland 1992). For the thyroid hormones, microradioimmunoassays requiring 5–20 μL of plasma were employed, as developed and described previously (Leatherland, Hilliard, Macey & Potter 1990).…”
Section: Methodsmentioning
confidence: 99%